Measurement of Liver Iron Concentration by MRI Is Reproducible. (22nd March 2015) - Alústiza, José María; Emparanza, José I.; Castiella, Agustín; Casado, Alfonso; Garrido, Adolfo; Aldazábal, Pablo; San Vicente, Manuel; Garcia, Nerea; Asensio, Ana Belén; Banales, Jesús; Salvador, Emma; Moyua, Aranzazu; et al.
Abstract : Purpose . The objectives were (i) construction of a phantom to reproduce the behavior of iron overload in the liver by MRI and (ii) assessment of the variability of a previously validated method to quantify liver iron concentration between different MRI devices using the phantom and patients. Materials and Methods . A phantom reproducing the liver/muscle ratios of two patients with intermediate and high iron overload. Nine patients with different levels of iron overload were studied in 4 multivendor devices and 8 of them were studied twice in the machine where the model was developed. The phantom was analysed in the same equipment and 14 times in the reference machine. Results . FeCl3 solutions containing 0.3, 0.5, 0.6, and 1.2 mg Fe/mL were chosen to generate the phantom. The average of the intramachine variability for patients was 10% and for the intermachines 8%. For the phantom the intramachine coefficient of variation was always below 0.1 and the average of intermachine variability was 10% for moderate and 5% for high iron overload. Conclusion . The phantom reproduces the behavior of patients with moderate or high iron overload. The proposed method of calculating liver iron concentration is reproducible in several different 1.5 T systems.